A therapist helping hand for walker-assisted gait rehabilitation: a pre-clinical assessment (2020)
Smart Walkers are robotic devices commonly used to improve physical stability and sensory support for people with lower limb weakness or cognitive impairments. Even though such devices offer continuous monitoring during physical rehabilitation, providing a tool to empower therapists might reduce their efforts and increase patient's safety during gait therapies. The implementation of remote-operation strategies enable therapy managers to remote control and assess the smart walker and user information. In this context, this paper presents a new strategy to control and perceive a walker-assisted gait therapy, by means of a haptic joystick with three operational modes. A set of path following tasks were implemented to validate the operational modes. The kinematic estimation error was calculated, and it was found a decrease in the error, when feedback modes were used. Likewise, results from an usability and acceptance questionnaire show better participant's understating of visual feedback mode, and higher effort perception under haptic feedback mode. This interaction strategy represents a potential joystick application as a safety and control interface in walker-assisted gait.